Auckland Island Teal Anas aucklandica aucklandica revisited - Moore, Peter J; Walker, Kath (Wildfowl, 1991)
The population of Auckland Island Teal on Ewing Island was surveyed in November 1989. A mark-recapture study on the coast repeated surveys conducted in 1982 and 1983. Thirty-three Teal were banded and the total population was estimated at 100-169. Seventy-eight Teal were counted along the shoreline of Adams Island. Allowing for birds that were inland or using stream habitats, this figure may represent a population of 160-220 birds. Teal were also seen on Enderby, Rose and Ocean Islands but not on Auckland Island, where they are probably excluded by cats and pigs. The surveys support previous estimates that there are probably less than 600 Teal on the Auckland Islands, and that the population is probably stable.